Effects of freezing on membranes and proteins in LNCaP prostate tumor cells - Wolkers, Willem F. (2006)
Fourier transform infrared spectroscopy (FTIR) and cryomicroscopy were used to define the process of cellular injury during freezing in LNCaP prostate tumor cells, at the molecular level. Cell pellets were monitored during cooling at 2°C/min while the ice nucleation temperature was varied between −3 and −10°C. We show that the cells tend to dehydrate precipitously after nucleation unless intracellular ice formation occurs. The predicted incidence of intracellular ice formation rapidly increases at ice nucleation temperatures below −4°C and cell survival exhibits an optimum at a nucleation temperature of −6°C. The ice nucleation temperature was found to have a great effect on the membrane phase behavior of the cells. The onset of the liquid crystalline to gel phase transition coincided with the ice nucleation temperature. In addition, nucleation at −3°C resulted in a much more co-operative phase transition and a concomitantly lower residual conformational disorder of the membranes in the frozen state compared to samples that nucleated at −10°C. These observations were explained by the effect of the nucleation temperature on the extent of cellular dehydration and intracellular ice formation. Amide-III band analysis revealed that proteins are relatively stable during freezing and that heat-induced protein denaturation coincides with an abrupt decrease in α-helical structures and a concomitant increase in β-sheet structures starting at an onset temperature of approximately 48°C.